(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The Research aims to study the scientific methods of selecting the best project in a specific environment. The selection of the best small project is an important step for any executive authority or contractor and it is essential for achieving a specific goal (whether it is a profit or provision of certain goods or any other objective). In order to have a true choice, the project evaluation will be the basis of choice. ؛ Project evaluation defined as the an organized assemblage of data about the activities characteristic and results of actions or activities, for determining its value. It can afford a plurality of significant information project’s outcomes; it is a systematic method of reflecting on and calculating the wealth of what is being done (i.e. project, events, and program). Evaluation is usually understood as a product or an activity taking place at the end of a project. However, evaluation should be considered as a process, occurring across all phases of a project, used for determining what does occurred and if the early project objectives have been achieved. The aim of this paper is to study the scientific approaches and steps to make a decision to select the best small projects in a specific environment for implementing within the constraints of the investor and the governorate strategic plan.